Analisis Gaya Kepemimpinan Transformasional Kepala Ruangan Dalam Meningkatkan Kinerja Perawat Dan Mutu Pelayanan Keperawatan: Literatur Review - Metilda Metilda; Elsa Agustina; Maria Magdalena D. B; Putri Rohmah A; Salu Aulia; Widya Nurhidayanti (LPPM Universitas Respati Indonesia, 2026)
The head of the room is a first-line manager who has a strategic role in managing nursing resources and ensuring the quality of nursing services. The transformational leadership style is considered effective because it is able to increase the motivation, commitment, and performance of nurses. This literature review aims to analyze the role of the head of room transformational leadership style in improving nurse performance and the quality of nursing services. The method used is literature review by examining national and international scientific articles published in the last five years through international journals and national journal portals. The results of the study show that transformational leadership is positively related to improving nurse performance, work motivation, job satisfaction, and the quality of nursing services. This leadership style also contributes to creating a conducive work environment and supporting patient safety. It can be concluded that the transformational leadership of the head of the room is an effective managerial strategy to improve nurse performance and the quality of nursing services.